MEMAHAMI HADIS-HADIS AF’ÂL AL RASÛL DAN TANAWWU’ AL IBÂDAH - Hafizzullah Hafizzullah (JIA (Jurnal Ilmu Agama), 2016)
The  life  of  Prophet  Muhammad  is  a  great  example  of  Muslims,  especially  his  actions. Yet, many Muslims do not fully comprehend the deeds of the Prophet Muhammad. They assume that every Prophet’s actions are an obligation or an option to follow. Though the careful studies on the  issue  have  elaborated  and  come  to  the  conclusion  that  not  every  that  Prophet  Muhammad’s action  have  to  follow.  The  Islamic  scholars  have  distributed  the  diversity  of  prophet  actions  and explained  the  content  of  the  law,  with  the  level  of  obligaion,  ibahah  (permition)  or  or  a  good example to follow from the actions of the Prophet Muhammad.